Biochemical and cardiovascular predictors of PIMS-TS risk in children after COVID-19 recovery: preliminary results of the LATE-COVID-Kids Study - Izabela Jatczak-Pawlik; Joanna Lewek; Elżbieta Czkwianianc; Agnieszka Blomberg; Natalia Krysiak; Krzysztof Zeman; Piotr Jankowski; Maciej Banach (Archives of Medical Science, 2022)
Introduction We aimed to characterize biochemical and cardiovascular predictors of paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) risk based on the data from the LATE-COVID-Kids study.